LiBr-coated Air Electrodes for Li-air Batteries - Yoshiya HAYASHI (The Electrochemical Society of Japan, 2021)
Li–air batteries (LAB) have a theoretical energy density as high as 3500 Wh kg−1; however, many problems remain to be addressed before their practical application. Introduction of a redox mediator (RM) is commonly applied to reduce the high overpotential of the air electrode (AE) during the charge process. We try to fix an RM on the AE by coating it with a slurry of carbon black and binder on a carbon paper substrate to enable us not only to suppress the shuttle effect but also to concentrate the RM on the surface of the AE where it works. We use LiBr as the RM in this study and compare two types of LAB cells: one with a LiBr-coated AE and the other with LiBr dissolved in the electrolyte solution. The cell with the LiBr-coated AE exhibits a better cell performance than that with the dissolved LiBr.